Iceland’s external affairs in the Middle Ages: The shelter of Norwegian sea power - Baldur Þórhallsson 1968- (2012)
Fræðigrein According to the international relations literature, small countries need to form an alliance with larger neighbours in order to defend themselves and be economically sustainable. This paper applies the assumption that small states need economic and political shelter in order to prosper, economically and politically, to the case of Iceland, in an historical context. It analyses whether or not Iceland, as a small entity/country in the Middle Ages (from the Settlement in the 9th and 10th centuries until the late 14th century) enjoyed political and economic shelter provided by its neighbouring states. Admitting that societies were generally much more self-sufficient in the Middle Ages than in our times, the paper argues that Iceland enjoyed essential economic shelter from Norwegian sea power, particularly as regards its role in securing external market access. On the other hand, the transfer of formal political authority from Iceland to the Norwegian crown was the political price paid for this shelter, though the Icelandic domestic elite, at the time, may have regarded it as a political cover. The country’s peripheral location shielded it both from military attacks from outsiders and the king’s day-to-day interference in domestic affairs. That said, the island was not at all unexposed to political and social developments in the British Isles and on the European continent, e.g. as regards the conversion to Christianity and the formation of dynastic and larger states. This paper claims that the analysis of the need for shelter needs to take into account the political and economical costs that may be involved in a shield. Also, it needs to address how external actors may solve the problem of internal order. Moreover, an analysis from the point of view of the advantages of political or military shelter needs to address the im portance of the extent of engagement of a small community, particularly a remote one, with the outside world. The level of engagement and the identity of the entity with which ...